An Narative Review on Achieving Data Governance in Indonesia Amidst Data Security Challenges - Widia Febriyani; Tien Fabrianti Kusumasari; Muharman Lubis (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
This article discusses strategies to achieve good data governance in Indonesia amidst data security challenges, including data security cases that have occurred in Indonesia. According to the IT Governance Institute (ITGI) in 2021, only 34% of companies in Indonesia have implemented good data governance standards. This indicates a gap in understanding between organizations, as they have not fully realized and understood the importance of data governance. This study used a narrative review as a methodology to evaluate relevant studies related to this topic. The findings show the importance of sustainable data governance and cybersecurity, but only a small portion of organizations in Indonesia have implemented data governance strategies or data intelligence solutions. This article highlights strategies to improve data security in data governance in Indonesia through a better understanding of information security practices. The Data Management Association (DAMA) International Guide to the Data Management Body of Knowledge (DMBOK) concept is used as a conceptual framework for this research. This article provides significant information on strategies to improve security practices in data governance and the safe use of data, which can improve economic well-being.